2005
DOI: 10.1016/j.cub.2004.12.078
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Spindles and Cleavage Planes Are Oriented Randomly in the Two-Cell Mouse Embryo

Abstract: Most experimental embryological studies performed on the early mouse embryo have led to the conclusion that there are no mosaically distributed developmental determinants in the zygote and early embryo (for example see [1-6]). It has been suggested recently that "the cleavage pattern of the early mouse embryo is not random and that the three-dimensional body plan is pre-patterned in the egg" (in [7] for review see [8-10]). Two major spatial cues influencing the pattern of cleavage divisions have been proposed:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 33 publications
5
42
2
Order By: Relevance
“…Central questions include how this apparently initial asymmetry is established in the early mouse embryo, and whether the underlying mechanism in this process is comparable to that operating in non-mammalian 'model' organisms, in which localized ('prepatterned') determinants play an essential role. Whereas recent reports (Gardner, 1997;Gardner, 2001;PiotrowskaNitsche et al, 2005;Torres-Padilla et al, 2007) claim the presence of 'prepatterning' in the mouse egg and preimplantation embryos reminiscent of non-mammals, our studies (Hiiragi and Solter, 2004;Motosugi et al, 2005) and those by others (Alarcon and Marikawa, 2003;Alarcon and Marikawa, 2005;Chroscicka et al, 2004;Kurotaki et al, 2007;Louvet-Vallee et al, 2005) provide evidence supporting a 'regulative' and 'mechanical constraint' (Alarcon and Marikawa, 2003;Kurotaki et al, 2007;Motosugi et al, 2005) model of blastocyst morphogenesis. In this model, the first embryonic polarity, the Em-Ab axis, is not established until the blastocyst cavity is localized at one end (the abembryonic pole), and its eventual position is determined by the spatial constraints imposed by the zona pellucida (ZP) in conjunction with the epithelial seal in the outer cell layer.…”
Section: Introductioncontrasting
confidence: 50%
“…Central questions include how this apparently initial asymmetry is established in the early mouse embryo, and whether the underlying mechanism in this process is comparable to that operating in non-mammalian 'model' organisms, in which localized ('prepatterned') determinants play an essential role. Whereas recent reports (Gardner, 1997;Gardner, 2001;PiotrowskaNitsche et al, 2005;Torres-Padilla et al, 2007) claim the presence of 'prepatterning' in the mouse egg and preimplantation embryos reminiscent of non-mammals, our studies (Hiiragi and Solter, 2004;Motosugi et al, 2005) and those by others (Alarcon and Marikawa, 2003;Alarcon and Marikawa, 2005;Chroscicka et al, 2004;Kurotaki et al, 2007;Louvet-Vallee et al, 2005) provide evidence supporting a 'regulative' and 'mechanical constraint' (Alarcon and Marikawa, 2003;Kurotaki et al, 2007;Motosugi et al, 2005) model of blastocyst morphogenesis. In this model, the first embryonic polarity, the Em-Ab axis, is not established until the blastocyst cavity is localized at one end (the abembryonic pole), and its eventual position is determined by the spatial constraints imposed by the zona pellucida (ZP) in conjunction with the epithelial seal in the outer cell layer.…”
Section: Introductioncontrasting
confidence: 50%
“…Other studies in mice suggested no prelocalization of developmental determinants in the early blastomeres and showed that the second polar body is not a reliable morphogenetic determinant for the first cleavage [47,48]. Some claim that there is no rotation of the spindle itself but a movement of the blastomeres [49]. From our study, it can be concluded that a non-tetrahedral arrangement of the blastomeres within the 4-cell stage human embryo may affect its subsequent development.…”
Section: Discussionmentioning
confidence: 40%
“…In our previous paper [14], even though mRNA encoding solely EGFP was injected at a concentration of 1 mg/ml, 36% of embryos could reach to morula stage. Moreover, although the design of the mRNA injected (coding sequences, UTRs and poly(A) tail) was different, other groups used 0.5 mg/ml of mRNA for injection, and it seems that morula/ blastocyst development was not affected [5,26]. Thus, the toxicity to embryonic development appears to depend on the types and amounts of exogenous proteins translated from the mRNA injected rather than the mRNA itself.…”
Section: Safety Of Fluorescence Microscopy For Embryo Developmentmentioning
confidence: 99%